2019
DOI: 10.1016/j.envexpbot.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the physiological and cellular effects of uranium on the root system of Arabidopsis thaliana

Abstract: Uranium (U) is a naturally occurring radionuclide that is toxic for plants. The aim of this study was to gain insights into the physiological and cellular responses of roots to U stress. We analyzed the effects of uranyl nitrate on the architecture and physiology of Arabidopsis thaliana roots using different staining procedures and reporter genes. Also, we examined the homeostasis of inorganic phosphate (Pi) and Fe during U stress. We showed that, at a sub-toxic dose, U stimulated the apex mitotic activity, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…[7][8][9][10][11] Uranium inhibits plant growth, modifies root growth and architecture, disrupts mineral nutrition and homeostasis, and affects photosynthesis. [12][13][14][15][16][17][18][19] At the cellular level, U induces nitric oxide and hydrogen peroxide production and triggers defence mechanisms against oxidative stress. 19,20 Also, U perturbs iron, phosphate and manganese homeostasis 9,14,21,22 and triggers important changes in the metabolome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11] Uranium inhibits plant growth, modifies root growth and architecture, disrupts mineral nutrition and homeostasis, and affects photosynthesis. [12][13][14][15][16][17][18][19] At the cellular level, U induces nitric oxide and hydrogen peroxide production and triggers defence mechanisms against oxidative stress. 19,20 Also, U perturbs iron, phosphate and manganese homeostasis 9,14,21,22 and triggers important changes in the metabolome.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19] At the cellular level, U induces nitric oxide and hydrogen peroxide production and triggers defence mechanisms against oxidative stress. 19,20 Also, U perturbs iron, phosphate and manganese homeostasis 9,14,21,22 and triggers important changes in the metabolome. 23 At the molecular level, U has been shown to alter the expression of genes involved in iron and phosphate homeostasis, hormone synthesis and signalling, and cell wall metabolism in Arabidopsis thaliana.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical toxicity of U is mainly caused by uranyl ions (UO2 2+ ), which are dissolved in the soil and water. U increases ROS production in cells and increases SOD expression, indicating that SOD is the first line of defense against U toxicity [55]. Increased ROS in cells induce lipid peroxidation and cause a decrease in oxidative stress markers such as CAT and GSH and disturb sulfhydryl homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Actinides and lanthanides, e.g., uranium and europium, are generally non-essential elements and are unlikely to have a special route for transport into plants; nonetheless, they can be taken up by plants and may interfere with normal metabolic processes. For instance, PTMs can replace essential metal ions from their binding sites in enzymes, damage sulfhydryl-group-containing proteins, accelerate the formation of reactive oxygen species, and trigger antioxidant defense mechanisms in plants (e.g., Weiler and Nover 2008 ; Serre et al 2019 ; Aranjuelo et al 2014 ). To overcome this unwanted chain of events, plants synthesize protective metal binding metabolites, store metal chelates in vacuoles or secrete them into the rhizosphere (Weiler and Nover 2008 ), and deposit defense polymers such as callose or lignin (Serre et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, studies exploring the underlying mechanisms of these interactions at the cellular level, or those investigating toxic metal speciation at the molecular level, are less common. A recent study described the physiological and cellular responses of Arabidopsis thaliana roots to U stress (Serre et al 2019 ); among several findings, the authors reported the deposition of the defense polymers callose and lignin in the roots due to uranium stress. Earlier studies of the interaction of uranium with plants revealed, for example, the importance of radionuclide speciation for the uptake and translocation of radionuclides in plants (e.g., Ebbs et al 1998 ; Laurette et al 2012a , 2012b ), as well as the effects of uranium on phosphate homeostasis regulation (Misson et al 2009 ; Berthet et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%